Surgical margins in head and neck cancer: Intra- and postoperative considerations. Issue 1 (February 2019) - Thomas Robbins, K.; Triantafyllou, Asterios; Suárez, Carlos; López, Fernando; Hunt, Jennifer L.; Strojan, Primož; Williams, Michelle D.; Braakhuis, Boudewijn J.M.; de Bree, Remco; Hinni, Michael L.; Kowalski, Luiz P.; Rinaldo, Alessandra; et al.
Abstract: Objective: To provide a perspective on the significance of recent reports for optimizing cancer free surgical margins that have challenged standard practices. Methods: We conducted a review of the recent literature (2012–2018) using the keywords surgical margin analysis, frozen and paraffin section techniques, head and neck cancer, spectroscopy and molecular markers. Results: Of significance are the reports indicating superiority of tumor specimen directed sampling of margins compared to patient directed (tumor bed) sampling for frozen section control of oral cancers. With reference to optimal distance between tumor and the surgical margin, recent reports recommended cutoffs less than 5 mm. Employment of new technologies such as light spectroscopy and molecular analysis of tissues, provide opportunities for a" real time" assessment of surgical margins. Conclusions: The commonly practiced method of patient directed margin sampling involving previous studies raises concern over conclusions made regarding the efficacy of frozen section margin control. The recent studies that challenge the optimal distance for clear surgical margins are retrospective and address patient cohorts with inherently confounding factors. The use of novel ancillary techniques require further refinements, clinical trial validation, and justification based on the additional resources.